2019
DOI: 10.3389/fnbeh.2019.00033
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Reduces Fear and Causes Drastic Hypomethylation of Arginine Vasopressin Promoter in Medial Extended Amygdala of Male Mice

Abstract: Testosterone reduces anxiety-like behaviors in rodents and increases exploration of anxiogenic parts of the environment. Effects of testosterone on innate defensive behaviors remain understudied. Here, we demonstrate that exogenous testosterone reduces aversion to cat odor in male mice. This is reflected as increased exploration of area containing cat urine when castrated male mice are supplied with exogenous testosterone. We also report that exogenous testosterone leads to DNA hypomethylation of arginine vaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Accordingly, T. gondii is found in the ejaculates of rats and several other species [48][49][50][51][52] (but not in mice [28]). Moreover, T. gondii increases the synthesis of testosterone [53], a testicular hormone that reduces fear and anxiety [54]. The extra testosterone is crucial for T. gondii effects, primarily through its interaction with the brain.…”
Section: T Gondii Infection Alters Host Hormonesmentioning
confidence: 99%
“…Accordingly, T. gondii is found in the ejaculates of rats and several other species [48][49][50][51][52] (but not in mice [28]). Moreover, T. gondii increases the synthesis of testosterone [53], a testicular hormone that reduces fear and anxiety [54]. The extra testosterone is crucial for T. gondii effects, primarily through its interaction with the brain.…”
Section: T Gondii Infection Alters Host Hormonesmentioning
confidence: 99%
“…AVP neurons in both regions highly co-express both AR and ERs indicating the presence of receptors through which E2 and DHT can produce these effects [235,241]. Exogenous T treatment has also been shown to cause DNA hypomethylation of the AVP promoter in the MeA and BST [242] and in vitro studies identified ERβ binding to 3β-diol as a potential regulator of the AVP 5'untranslated region [243].…”
Section: Arginine Vasopressinmentioning
confidence: 99%
“…In rats, testosterone creates an epigenetic change within the bed nucleus of stria terminalis in the form of DNA hypomethylation on the AVP promotor [33]. Similarly, AVP promotor in mice MePD undergoes DNA hypomethylation in response to testosterone [56]. These observations provide a molecular link between male gonadal hormones and ongoing plasticity in adult MePD-AVP+ neurons.…”
Section: Discussionmentioning
confidence: 91%
“…This brain region also shows low numbers of oxytocin-containing fibers in male mice, with dense OXTR distribution [70][71][72]. Furthermore, castration simultaneously reduces the amount of AVP transcription [56] and OXTR binding density [73] within the medial amygdala, while leaving hypothalamic sources of the AVP intact. These observations suggest that the effects of AVP in MePD might result from the interaction of AVP-containing axons and OXTR present in the vicinity.…”
Section: Discussionmentioning
confidence: 98%